Public‐Private Collaboration, Hybridity and Social Value: Towards New Theoretical Perspectives - Quélin, Bertrand V.; Kivleniece, Ilze; Lazzarini, Sergio (Journal of Management Studies, 2017)
AbstractFocusing on the collaboration intersecting public, non‐profit and private spheres of economic activity, we analyse the conceptual forms of hybridity embedded in these novel inter‐organizational arrangements, and link them to different mechanisms of creating social value. We first disentangle alternative notions of hybrid arrangements in existing literature by proposing a conceptual typology on two theoretically complementary yet distinct dimensions: hybridity in governance and hybridity in organizational logics. We show how both forms of hybridity can jointly occur in complex public‐private and cross‐sector collaborations, and propose the notion of value as a crucial bridging point between these perspectives. Crucially, we develop a conceptual framework on key theoretical mechanisms leading to economic and social value in these inter‐organizational collaborations. Our work deepens the understanding of how diverse, hybrid forms of collaboration can create value and builds critical links between previously disparate streams of literature on public‐private interaction, cross‐sector collaboration and social enterprises.